Causes of mandibular fractures and different types of treatment resulting from third molar extractions: Integrative review (Research, Society and Development, 2024)
The aim of this integrative review was to analyze scientific studies on the most common types of mandibular fractures resulting from third molar extraction. Mandibular fractures constitute a significant portion of facial fractures, and their treatment has been widely discussed due to the various options with favorable prognosis and treatment success. The descriptors used were Maxillomandibular Fractures, Oral Surgery, and Intraoperative Complications. The databases consulted were LILACS, SCIELO, and PUBMED, with a search for studies published between 2014 and 2024 in English and Portuguese. For article selection, steps were followed that included reading titles and abstracts, excluding similar articles, those that did not address the proposed topic, were not available in the mentioned languages, or were incomplete or not free. Out of the 238 articles initially selected, 324 articles were excluded, resulting in the selection of 4 articles that met the inclusion criteria for full reading. It was concluded that the surgical approach to mandibular fractures should ensure anatomical correction and adequate fixation to minimize complications. Treatment can be surgical or non-surgical, depending on the type of fracture, and various techniques are available to ensure success and restoration of masticatory function. The literature presents a variety of studies demonstrating different surgical approaches to mandibular fractures, aiding in understanding and choosing the most appropriate technique.